Dinamika Politik Hukum Keanggotaan Majelis Permusyawaratan Rakyat: Unikameralisme dalam Bayang-Bayang Sistem Bikameral - Rupertus Arvinci Ngabut; Ariawan Gunadi (CV Rewang Rencang, 2024)
The structural changes to the People's Consultative Assembly (MPR) following the 1945 Constitution amendment have created ambiguity in Indonesia’s representative system. The MPR, consisting of the House of Representatives (DPR) and the Regional Representative Council (DPD), does not fully reflect true bicameralism due to the unequal authority between the two chambers. Using a legal-political approach, this study examines the implications of MPR membership for constitutional dynamics and power balance. Findings indicate that regulatory changes and constitutional practices influence MPR’s role and checks and balances in legislation and policymaking, highlighting the need for reforms to strengthen the representative system.